EDUKASI BAHAYA SAMPAH PLASTIK KEPADA MASYARAKAT PESISIR DI PANTAI PULOT, KECAMATAN LEUPUNG, KABUPATEN ACEH BESAR - Rika Astuti; Hayatun Nufus (Marine Kreatif, 2022)
Plastic waste is one type of waste that is very dominant in its use in everyday life. The nature of plastic that is light, strong, durable and cheap causes the use of plastic to continue to increase, from the nature of this plastic it makes plastic very dangerous for the environment which has the potential to be a contaminant, besides that plastic has properties that are not easily decomposed in soil and water, so it can settle and accumulated over a long period of time. The Pulot Beach area is one of the tourist attractions in Aceh Besar, with beautiful natural panoramas and the potential for fisheries in this area is also very potential, so many people visit this area. The high number of tourists visiting the Pulot area can have a negative impact in the form of plastic waste that has the potential to reduce the quality of the coastal and marine environment as well as the preservation of the surrounding environment. The purpose of this service is to provide understanding, knowledge and direction to the coastal community of Gampong Pulot the importance of human awareness of the cleanliness of the sea by not throwing garbage on the beach. This service activity is carried out for one day, namely on Thursday, October 28, 2021 at 09:00 to 12:00 WIB, located at Pulot Beach, Leupung District, Aceh Besar Regency. persuasive education and direct practice on how to collect waste, and sort plastic waste and weigh waste. The output obtained after this service activity is the emergence of awareness and initiative from the community and visitors not to throw plastic waste carelessly, so that the preservation of healthy beaches and seas is free from plastic waste.